Pembentukan Karakter Peduli dan Berbudaya Lingkungan bagi Peserta Didik di Madrasah Melalui Program Adiwiyata - Hafida, Nur; Wahid, Abdul Hamid (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
This paper presents the formation of caring and environmentally friendly characters for students in the madrasah. Along with the increasing number of environmental problems, it is important and urgent to intensify the environmental care movement in the context of education, so that the green school and green curriculum concept is created, which is realized through the adiwiyata program. This study used a qualitative method with a case study, with a research site at Probolinggo MTs Negeri 1 Probolinggo. The results showed that, the challenges and character formation of caring and cultured students include; the first is the low level of public support for the adwiyata program, both parents' support that has not been optimal in realizing caring and cultured madrasas. The three times changes that are increasingly advanced make all human needs easily met with the help of machines. While the strategy of character building for caring and environmentally friendly students through the adiwiyata program is carried out through; the first is the formation of characters integrated in learning activities, second through the formation of madrasa culture, the third is extracurricular activities, fourth involves families and communities